Multifaced roles of cannabinoid therapy in cancer: balancing analgesia, antitumor potential, and systemic toxicity - Creanga-Murariu, Ioana; Ciorpac, Mitica; Gogu, Raluca-Maria; Pricope, Cosmin-Vasilica; Bild, Veronica; Ababei, Daniela-Carmen; Filipiuc, Leontina-Elena; Szilagyi, Andrei; Josan, Claudiu-Laurentiu; Caruntu, Irina-Draga; Lozneanu, Ludmila; Timofte, Andrei; et al. (Frontiers in Pharmacology, 2025)
IntroductionCannabinoids hold promise in oncology for symptom relief and antitumor effects, though concerns about safety and efficacy persist. This study assessed the impact of JWH-182 and phytocannabinoids NC1 – Cannabixir® Medium dried flowers and NC2 – Cannabixir® THC full extract, in a murine breast cancer model with paclitaxel-induced peripheral neuropathy (CIPN).MethodsFemale BALB/c mice with breast tumors received paclitaxel alone or combined with cannabinoids, and outcomes included pain sensitivity, tumor progression (imaging and histopathology), cachexia (body weight, food intake, imaging), as well as hematological and organ toxicity profiles.ResultsAll cannabinoids alleviated neuropathic pain, with NC1 most effective for central and thermal protection (72% and 100%, p < 0.0001), NC2 showing strong central and mechanical benefit (>60% and >33%), and JWH-182 intermediate (∼50%). Tumor growth was not significantly altered, but metastasis incidence was 41.7% for NC1, 58.3% for NC2, compared with 70% for PTX, suggesting antitumoral activity. Effects on cachexia were modest, JWH-182 tended to improve food intake, whereas NC1 and NC2 reduced it, yet body weight remained stable and significant muscle loss was observed only with NC2 (p < 0.05). Hematology showed immunomodulatory effects, with cannabinoids reversing lymphopenia (p = 0.0005), raising monocytes and neutrophils, and partly restoring platelets. Toxicity was highest with NC2 (renal and hepatic injury), moderate with NC1, and lowest for kidney with JWH-182 but with greater hepatic inflammation.ConclusionCannabinoids show potential in oncology by relieving CIPN and influencing tumor dynamics, with mostly neutral effects on cachexia. GMP-certified formulations enhance translational value, though safety concerns warrant further study.